Effects of Various Stabilizers on Sensorial Quality of Yoghurt - Bhattarai, Nirmala; Pradhananga, Mahalaxmi; Mishra, Shyam Kumar (Sunsari Technical College Journal, 2016)
This research was aimed to preserve the yoghurts using stabilizers without refrigeration in terms of syneresis and sensory analysis. Yoghurts were prepared using three stabilizers viz., gelatin, carboxymethylcellulose and sodium alginate and a control (without stabilizer). For which set type yoghurt was prepared with 2% starter culture inoculation and was incubated at 43⁰C for 3 hours and was stored at 5-7⁰C. Statistical analysis of all the treatments showed that 0.2 % stabilizer containing samples were significantly superior (p<0.05). The best samples with stabilizers containing 0.2% were again compared with control. From this, 0.2% gelatin added sample had significantly superior (p<0.05) scores. Shelf life of the sample was observed and it was compared with control at refrigerated condition. Sensorial gelatin added sample was best up to eleventh days while the control was best up to seventh days. Gelatin added sample showed less syneresis compared to control and adding stabilizer seems slower the acid development and syneresis of yoghurt in terms of storage time. Sunsari Technical College Journal 2015,2(1):7-12